2005
DOI: 10.17129/botsci.1705
|View full text |Cite
|
Sign up to set email alerts
|

Distribución geográfica y afinidad por el sustrato de las algas verdes (Chlorophyceae) bénticas de las costas mexicanas del Golfo de México y Mar Caribe

Abstract: The geographical distribution of the green benthic seaweeds from the Mexican coasts of the Gulf of Mexico and the Caribbean Sea was analyzed by means of a data bank that includes 98 taxonomic publications that appeared in the 1846 - 2000 period, based on Jaccard’s index. In total, 169 species with 49 genera were recorded, with the highest species richness corresponding to Cladophora (26 species) and Caulerpa (16). Over 70.8% of all the phycoflora was confirmed based on 69 species collected by the authors in 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
0
8
0
21
Order By: Relevance
“…Es importante resaltar que más de la mitad (53.9%) de las especies de Chlorophyta de la costa atlántica y del Pacífico tropical de México han sido recolectadas en sustrato rocoso. Garduño-Solórzano et al (2005), Mateo-Cid y Mendoza-González (1991,2001,2012) y Mendoza-González et al (2011) señalan que este sustrato expuesto al oleaje es el lugar donde se localiza una gran diversidad de algas marinas. La textura, el grado de dureza y el color de las rocas influyen sobre las comunidades algales.…”
Section: Discussionunclassified
“…Es importante resaltar que más de la mitad (53.9%) de las especies de Chlorophyta de la costa atlántica y del Pacífico tropical de México han sido recolectadas en sustrato rocoso. Garduño-Solórzano et al (2005), Mateo-Cid y Mendoza-González (1991,2001,2012) y Mendoza-González et al (2011) señalan que este sustrato expuesto al oleaje es el lugar donde se localiza una gran diversidad de algas marinas. La textura, el grado de dureza y el color de las rocas influyen sobre las comunidades algales.…”
Section: Discussionunclassified
“…This fact may be related to the hard and stable substrate, which allows the establishment of green algae (Santelices 1977), an appropriated environment for the development of a great number of tropical seaweeds like Bryopsidales and Dasycladales (Lüning 1990). Moreover, sites with sandy substrate without sea-grass are lower richness; this may be because this type of bottom is unstable because the removal of substrate by mechanical force of water can inhibit the establishment and development of new thalli of marine green algae (Santelices 1977;Garduño-Solórzano et al 2005). In addition, these sample sites are in brackish areas (Herrera-Silveira 2006), which are less favorable for the development of marine green algae (Ulvophyceae) because such algae are better adapted to fully marine conditions (Lüning 1990;Lobban and Harrison 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Taylor 1960;Aguilar Rosas et al 1998;Mateo-Cid and Mendoza-González 2007) indicated that on rocky substrates a great diversity of seaweed can develop. Garduño-Solórzano et al (2005) referred to hardness and the degree of compactness of substrate has an important role in the distribution of algae. In contrast, the epiphytic flora is characterized by filamentous thalli, small size and short life cycles (Hoek 1982;Hoek et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Se dispone de pocos estudios publicados sobre datos moleculares de la especie y se refieren a organismos de la región europea (Países Bajos, Choi, Kraft, Lee y Saunders, 2002;Lin et al, 2001). Esta observación es interesante, ya que será necesario compararlos con los ejemplares americanos y deslindar provincias geográficas (Europa, golfo de México y Caribe, Garduño-Solórzano, Godínez-Ortega y Ortega, 2005). Lin et al (2001) señalan que H. hypoglossoides se encuentra dentro del grupo Hypoglossum con ausencia de células intercalares en todas las filas de células y células de tercer orden que logran llegar al margen de la fronda.…”
Section: Diagnosisunclassified